Environmental impacts of reject brine disposal from desalination plants - Anders, Cláudio Rodrigues; Fernandes, Cleyton Dos Santos; Dias, Nildo da Silva; Gomes, Jonath Werissimo da Silva; Melo, Mikhael Rangel de Souza; de Souza, Bruno Goulart Azevedo; Souza, Ana Cláudia Medeiros; de Sousa Júnior, Francisco Souto (Elsevier, 2020)
The chemical composition and the impacts of reject brine disposal from desalination plants on soils of the west of Rio Grande do Norte, Brazil, were evaluated. Soil samples in the 0.0–0.2 and 0.2–0.4 m profiles were collected at three points of reject brine influences (0, 0.8 and 1.6 m of reject brine site) and a point in the native forest (without the influence of reject brine) for chemical characterization. The analysis showed that 25% of the native forest soils have problems of salinity and/or sodicity, suggesting that salt-affected soils already existed in some communities even without the disposal of brine. The variability between the results on analysis of soil chemical properties from study lands suggests an individual assessment of potential risk of soil salinization due to the disposal of reject brine from desalination plants.
Keywords: Brine discharge; Desalination; Reverse osmosis; Salinity and sodicity; Soil saline